Fast evolution of SARS-CoV-2 BA.2.86 to JN.1 under heavy immune pressure - Yang, Sijie; Yu, Yuanling; Xu, Yanli; Jian, Fanchong; Song, Weiliang; Yisimayi, Ayijiang; Wang, Peng; Wang, Jing; Liu, Jingyi; Yu, Lingling; Niu, Xiao; Wang, Jing; et al. (The Lancet infectious diseases, 2024)
Considering that the L455 is predominantly located at the epitope of receptor binding domain Class 1 antibodies, as indicated by earlier research, our study further examined the evasion capabilities of JN.1 in response to eight XBB.1·5-neutralising class 1 monoclonal antibodies.7 Pseudovirus neutralisation assays showed that the addition of the L455S mutation enhanced JN.1's ability to evade class 1 antibodies (figure D). In summary, JN.1, by inheriting BA.2.86's antigenic diversity and acquisition of L455S, rapidly achieved extensive resistance across receptor binding domain class 1, 2, and 3 antibodies,1 and showed higher immune evasion compared with BA.2.86 and other resistant strains like HV.1 and JD.1·1, at the expense of reduced human ACE2 binding. [...]strains could survive and transmit at low levels since their antigenic difference would allow them to target distinct populations compared with dominant strains and have the potential to quickly accumulate highly immune-evasive mutations at the cost of human ACE2 binding capabilities.